Polychromie et décors moulés et appliqués - Sophie Guillot de Suduirot (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
These thoughts on terminology are part of our studies of sculpture in Germany, the Early Netherlands and Northern France of the XVe and XVIe centuries.The term polychromy now refers to that which covers the material of the sculpture.  It concerns all of the layers, including metal leaves (gold, silver, Zwischgold leaf, tin…) and applied decoration. In place of the German terms Pressbrokat or Pressbrokat-Applikationen (« applied brocade »), created in the XXe century in reference to textiles improperly called brocades, we propose décors moulés et appliqués, « cast and applied decorations », more correct and explicit. These relief decorations often evoke Italian silk velvets with gold threads and small curls.